Epibrassinolide alters PI3K/MAPK signaling axis via activating Foxo3a-induced mitochondria-mediated apoptosis in colon cancer cells - Çoker Gürkan, Ajda; Palavan Unsal, Narcin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; COŞKUN, DENİZ (Elsevier Inc, 525 B Street, Ste 1900, San Diego, Ca 92101-4495 Usa, 2015)
Epibrassinolide (EBR), a steroid-derived plant growth regulator, has been recently suggested as an apoptotic inducer in different cancer cells. In this experimental study, we investigated the potential apoptotic effect of EBR on stress-related and survival signaling molecules in colon carcinoma cells. EBR decreased cell viability and colony formation in HCT 116 and HT-29 colon carcinoma cells. The inactivation of PI3K/AKT by EBR treatment led to upregulation of Foxo3a, which in turn induced apoptosis in HCT 116 and HT-29 cells. In addition, the upstream non-receptor protein tyrosine kinase Src was found elevated allowing to the upregulation of p38, stress-activated protein kinase/Jun amino-terminal kinase and extracellular signal-regulated kinase 1/2 and their target genes c-jun, c-fos and c-myc in a time-dependent manner in HCT 116 cells within 48 h. The alterations in PA metabolism caused intracellular PA pool decrease. The upregulation of pro-apoptotic Bak, Bax, Puma and Bim were accompanied with the decrease in Mcl-1 in HCT 116 and Bcl-x(L), expression profiles in HT-29 following 48 h EBR treatment. We suggest that the upregulation of Bim expression levels might be related with one of the PI3K/AKT target transcription factor Foxo3a, which was dephosphorylated by EBR treatment in HCT 116 and HT-29 cells. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Epibrassinolide; Polyamines; Apoptosis; Colon cancer; PI3K; AKT; Foxo3a; Forkhead Transcription Factor; Polyamine Catabolism; Cycle Arrest; Map Kinases; Pathways; Jnk; P53; Brassinosteroids; Inhibition; Expression